Socio-environmental awareness and the implementation of strategic planning: a Case study of Coopersol in Jales - Silva, Vania da; Lima , Edy Carlos Santos de; Lima, Greice Kelli Lopes Santos de; Rodrigues , Rivelino; Baio , Simone Pereira da Silva (Scientific Journal ANAP, 2025)
Objective – To characterize and analyze the perception of professionals at the Regional Cooperative of Solid Waste Collectors – Coopersol regarding socio-environmental issues, as well as to identify whether a strategic planning process was developed and implemented. Methodology – This is a case study conducted at Coopersol, located in the municipality of Jales/SP. Data were collected between April and June 2024 through a questionnaire administered to all 23 cooperative members and an interview with the cooperative’s president. Originality/Relevance – The study contributes to filling gaps related to the perception of waste pickers about their socio-environmental role and the strategic management of recycling cooperatives—a relevant topic given the increase in waste generation and the need for sustainability in these organizations. Results – It was observed that the cooperative members acknowledge their role in environmental preservation, although they lack the technical knowledge necessary for risk mitigation. The importance of strategic planning was highlighted as essential for the continuity and effectiveness of the cooperative’s actions. Theoretical/Methodological Contributions – This work highlights the need to incorporate strategic management practices into grassroots cooperatives, contributing theoretically to the discussion on organizational sustainability and methodologically through the use of direct research instruments. Social and Environmental Contributions – The findings indicate that recycling cooperatives are important generators of employment and income, as well as promoters of environmental preservation, provided they receive the necessary support to ensure safe and sustainable working conditions.